Dzielimy się doświadczeniemSurgical treatment of false aneurysm and perivalvular abscess in bacterial endocarditis - Widenka, Kazimierz; Mazur, Witold; Stącel, Tomasz; Kolowca, Maciej; Szymanik, Izabela; Kurowicki, Arkadiusz; Deja, Marek; Woś, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The aim of this paper was to describe cases of using a stentless valve in reoperation in bacterial endocarditis. The first patient had a pseudoaneurysm of the distal anastomosis due to bacterial endocarditis. The date of operation was postponed because of haemorrhagic stroke with hemiparesis. The operation was performed in deep hypothermic circulatory arrest. The postoperative period was uneventful. During the operation of the second patient a stentless valve was used to treat bacterial endocarditis after root replacement and mechanical prosthesis implantation. Third degree heart block was observed in the postoperative period. A permanent pacemaker was inserted. Homograft implantation due to prosthetic valve endocarditis is the procedure of choice. Because of its limitation in accessibility, an alternative method can be stentless valve implantation.